Implantación de la contabilidad en minimarket El Flaco, del cantón Cascales, provincia de Sucumbios, periodo enero a marzo del 2015 - Buñay Quintanilla, Amanda Maribel (2016)
The paper titled IMPLEMENTATION OF ACCOUNTING IN MINIMARKET THE SKINNY, CANTON CASCALES, Sucumbios province, January-March period of 2015, is aimed at proposing accounting tools that facilitate their own generating reliable information to improve economic performance of the company. Additional comply with one of the requirements of the Academic Board of the National University of Loja before graduation and obtaining engineering degree in Accounting and Auditing. CPA. In the development is part of the needs of the company, having emerged as main objective the implementation of an accounting process for decision-making, primarily theoretical foundations that sustain for the development and support of it are presented in the practice the system of permanent account was applied; Starting from an initial inventory that served to determine the stocks of all assets owned by the company, then a Plan and Manual of Accounts which facilitated the identification and proper use of the accounts are drawn up, main and auxiliary registers are applied to centralize and quantify the economic movement finally presenting the financial statements that show clearly and realistically the economic performance in the period. Once applied the accounting process, it is concluded that the practical application yielded real results through the financial statements, so it is recommended to implement the accounting as a tool that contributes to have better control of the operations carried out within the company; The journal designed to apply in order to determine the cash inflows and outflows; make constant updating of inventory as this will allow to pinpoint the assets, rights and obligations that owns the entity; and use the data bank boards to the movement of products, all with the aim of increasing corporate profitability obtained at the end of an economic cycle, in the medium or long term.